Effects of Cheliped Amputation on the Personality of Crayfish - Leiyu Lu; Li Su; Mengdi Si; Guangyao Wang; Chunlin Li (Animals, 2024)
Animal personality, which describes inter-individual differences and intra-individual consistency in behaviors across time and contexts, has been widely observed and has significance for both ecology and evolution. Morphological modifications, particularly during early life stages, may highly influence animal behavior in adulthood; thus, exploring this relationship can elucidate personality development throughout ontogeny. In this study, we reared juvenile crayfish (Procambarus clarkii) with different degrees of cheliped mutilation and explored their personality patterns, including exploration and aggression, when they reached sexual maturity. Male crayfish showed repeatability in exploration, and both sexes showed repeatability in aggression. We observed no significant correlation between the two behavioral traits, indicating the absence of behavioral syndromes. Moreover, exploration did not differ according to the type of mutilation, but crayfish with more intact chelipeds were more aggressive, and males were more aggressive than females. These results indicate that cheliped mutilation may modify the average levels of personality traits associated with competition or self-defense. Our study provides insights into how morphological modifications may shape animal personalities in adulthood.